The reality of the peasants in the eyes of Iraqi poets In the first half of the twentieth century - Hassoon Nahay, Mohammed (Al-Adab Journal, 2019)
The farmer in Iraq in general and in the South in particular has been subjected to great injustice and obvious injustice, not even taking his position as a human being, which allowed the feudalism, which is stripped of all human values ​​and feelings, to bring it down to perpetual humiliation and torment. Equity leads us to say: The attitude of the Iraqis was great according to all standards and at the forefront of the literature, as many of them addressed the injustice of feudalism and did not hesitate to name some of their names despite the feudal favor and the intensity of all the affairs of the country. As for the poets, especially the poets of Najaf, they left us a wonderful poetic picture of the injustice of feudalism to the peasant because of the state of consciousness that prevailed in the Najafi society, and this activity was not limited to the poets of Najaf, but there is a large group of poets of Iraq took on the responsibility of the wolf On the rights of the vulnerable peasant and the anti-feudal feudalism. The popular poetry also has a clear role, as it is not so, which is closer to reality and more appropriate to the feelings of people, especially that it is far from the complexity and in tune with the suffering of the peasants exposed to the cruelty of feudalism.